Psychometric properties of the Malay Version of the Hospital Anxiety and Depression Scale: A study of husbands of breast cancer patients in Kuala Lumpur, Malaysia - Yusoff, Nasir; Low, Wah Yun; Yip, Cheng Har (Asian Pacific Organization for Cancer Prevention, 2011)
The main objective of this paper is to examine the psychometric properties of the Malay Version of the Hospital Anxiety and Depression Scale (HADS), tested on 67 husbands of the women who were diagnosed with breast cancer. The eligible husbands were retrieved from the Clinical Oncology Clinic at three hospitals in Kuala Lumpur, Malaysia. Data was collected at three weeks and ten weeks following surgery for breast cancer of their wives. The psychometric properties of the HADS were reported based on Cronbach' alpha, Intraclass Correlation Coefficients (ICC), Effect Size Index (ESI), sensitivity and discriminity of the scale. Internal consistency of the scale is excellent, with Cronbach's alpha of 0.88 for Anxiety subscale and 0.79 for Depression subscale. Test-retest Intraclass Correlation Coefficient (ICC) is 0.35 and 0.42 for Anxiety and Depression Subscale, respectively. Small mean differences were observed at test-retest measurement with ESI of 0.21 for Anxiety and 0.19 for Depression. Non-significant result was revealed for the discriminant validity (mastectomy vs lumpectomy). The Malay Version of the HADS is appropriate to measure the anxiety and depression among the husbands of the women with breast cancer in Malaysia.